Critical intelligence studies: introduction to the special issue. Issue 4 (7th June 2021) - Bean, Hamilton; de Werd, Peter; Ivan, Cristina
ABSTRACT: This introduction to the special issue describes recent developments in intelligence studies that support the establishment of a critical intelligence studies (CIS) subfield. It reviews work published both within and outside the field of intelligence studies to outline the general commitments and orientations of CIS. It concludes by previewing the essays collected for this special issue.